Full and Incomplete Fetal Alcohol Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
The clinical features and hospitalization rates of children with full or incomplete fetal alcohol syndrome (FAS) were compared in retrospective case-controlled studies of affected Northern Plains American Indian children attending Aberdeen Area Indian Health Service hospitals, South Dakota.